Analysis Brand Image, Product Quality, And Brand Ambassador On Customer Purchase Decision For Scarlett Whitening Product In Sidoarjo - Rifka Ulinnuhya Annafa; Wisnu Panggah Setiyono; Herlinda Maya Kumala Sari (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The tight business competition between companies today means that all companies want to be the best to attract the attention of consumers. Scarlett Whitening is a company that reached a sales record of 1 billion in 4 hours when collaborating with Exo. EXO is used as a strategy to attract consumers to buy this product. However, Scarlett Whitening consumers do not only look at the type of product or quality, consumers also look at the advantages in terms of the brands that are most popular. This research aims to examine the influence of Brand Image, Product Quality, and Brand Ambassador on Consumer Purchasing Decisions in Sidoarjo. This type of research is quantitative using descriptive statistical data analysis methods and testing methods including: Validity Test, Reliability Test, Classical Assumption Test, and Hypothesis Test. Data collection took the form of distributing questionnaires which produced valid data for 100 samples. The results show that the brand image variable has an insignificant positive influence. Meanwhile, the product quality and brand ambassador variables have a positive and significant effect.